Human Papillomavirus Type Distribution in Invasive Cervical Cancer and High-Grade Cervical Intraepithelial Neoplasia Across 5 Countries in Asia. Issue 1 (1st January 2013) - Quek, Swee Chong; Lim, Boon Kiong; Domingo, Efren; Soon, Ruey; Park, Jong-Sup; Vu, Thi Nhung; Tay, Eng Hseon; Le, Quang Thanh; Kim, Young-Tak; Vu, Ba Quyet; Cao, Ngoc Thanh; Limson, Genara; et al.
Abstract : Objective: Independent, prospective, multicenter, hospital-based cross-sectional studies were conducted across 5 countries in Asia, namely, Malaysia, Vietnam, Singapore, South Korea, and the Philippines. The objectives of these studies were to evaluate the prevalence of human papillomavirus (HPV) types (high risk and others including coinfections) in women with invasive cervical cancer (ICC) and high-grade precancerous lesions. Methods: Women older than 21 years with a histologic diagnosis of ICC and cervical intraepithelial neoplasia [CIN 2 or 3 and adenocarcinoma in situ (AIS)] were enrolled. Cervical specimens were reviewed by histopathologists to confirm the presence of ICC or CIN 2/3/AIS lesion and tested with short PCR fragment10 -DNA enzyme immunoassay-line probe assay for 14 oncogenic HPV types and 11 non-oncogenic HPV types. The prevalence of HPV 16, HPV 18, and other high-risk HPV types in ICC [including squamous cell carcinoma (SCC) and adenocarcinoma/adenosquamous carcinoma (ADC/ASC)] and CIN 2/3/AIS was estimated. Results: In the 5 Asian countries, diagnosis of ICC was confirmed in 500 women [SCC (n = 392) and ADC/ASC (n = 108)], and CIN 2/3/AIS, in 411 women. Human papillomavirus DNA was detected in 93.8% to 97.0% (84.5% for the Philippines) of confirmed ICC cases [94.0%–98.7% of SCC; 87.0%–94.3% (50.0% for the Philippines) of ADC/ASC] and in 93.7% to 100.0% of CIN 2/3/AIS. The most common types observed among ICC cases were HPV 16 (36.8%–61.3%), HPV 18 (12.9%–35.4%), HPV 52 (5.4%–10.3%), and HPV 45 (1.5%–17.2%), whereas among CIN 2/3/AIS cases, HPV 16 (29.7%–46.6%) was the most commonly observed type followed by HPV 52 (17.0%–66.7%) and HPV 58 (8.6%–16.0%). Conclusions: This article presents the data on the HPV prevalence, HPV type distribution, and their role in cervical carcinogenesis in 5 Asian countries. These data are of relevance to public health authorities for evaluating the existing and future cervical cancer prevention strategies including HPV-DNA testing–based screening and HPV vaccination in these Asian populations.